Adding Semantics to Business Intelligence: Towards a Smarter Generation of Analytical Tools - Sell, Denilson; Silva, Dhiogo Cardoso da; Ghisi, Fernando Benedet; Napoli, Márcio; Todesco, José Leomar (IntechOpen, 2012)
None